Konservasi Hutan Berbasis Kearifan Lokal di Desa Tigawasa, Kecamatan Banjar, Kabupaten Buleleng - Candraningsih, Ida Ayu Komang; Pujaastawa, Ida Bagus Gde; Sudiarna, I Gusti Putu (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p06, 2018)
This research aims to examine the environmental conservation system based on local wisdom in Tigawasa Village, Banjar District, Buleleng Regency which is one of the villages belonging to the Bali Aga or Bali Kuna Village in Bali. The problems in this study focused on local forms of wisdom related to forest conservation and their implications for ecological and economic aspects. The theory used in this research is the interpretive theory by Connie Geertz and the etnoecological approach by Conklin and Frake. The concept used in this research is conservation, forest and local wisdom. The research method used is qualitative method, with complete data of observation, interview, literature study and document examination.   The results of the research revealed that the conservation activities of customary forests conducted by the people of Tigawasa Village are based on the local wisdoms of the ancestors that are still maintained. These local wisdoms include community conceptions of the existence of forest areas, the myths that develop in the community, forest-related ritual practices and written and non-written regulations on customary forests. Tigawasa Village community considers that the customary forest in the village is a sacred area that should not be entered or utilized other than for the purposes of traditional ceremonies, so that the forest ecosystem is maintained. The implications of forest conservation based on local wisdom are the preservation of the environment of the local forest and the development of economic opportunities in the form of forest management as an ecotourism attraction.